1990
DOI: 10.1016/0020-7225(90)90054-m
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic boundary layer solutions for mixed convection from a vertical surface in a micropolar fluid

Abstract: Abstrad-Using the theory of micropolar fluids due to Eringen, asymptotic boundary layer solutions are presented to study the combined convection from a vertical semi-infinite plate to a micropolar fluid. Consideration is given to the region close to the leading edge as well as the region far away from the leading edge. Numerical results are obtained for the velocity, angular velocity and temperature distribution. The missing wall values of the velocity, angular velocity and thermal functions are tabulated. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…For viscous fluid flow (D ¼ x ¼ 0) and g ¼ 0 equation (14) reduces to the equation (6) of Cortell [48] and equation (8) of Hayat et al [45] if we replace our magnetic field parameter M by M ¼ 2n/n þ 1 where n is the nonlinear stretching parameter (see Cortell [48]). To assess the accuracy of the present code, we tabulate the values of Àf 00 (0) for a viscous fluid in Table 1 and compare them with the numerical results reported by Cortell [48] and Hayat et al [45].…”
Section: Code Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For viscous fluid flow (D ¼ x ¼ 0) and g ¼ 0 equation (14) reduces to the equation (6) of Cortell [48] and equation (8) of Hayat et al [45] if we replace our magnetic field parameter M by M ¼ 2n/n þ 1 where n is the nonlinear stretching parameter (see Cortell [48]). To assess the accuracy of the present code, we tabulate the values of Àf 00 (0) for a viscous fluid in Table 1 and compare them with the numerical results reported by Cortell [48] and Hayat et al [45].…”
Section: Code Verificationmentioning
confidence: 99%
“…Many investigators have studied and reported results for micropolar fluids. The notable contributions are from Ebert [6], Jena and Mathur [7], Soundalgekar and Takhar [8], Gorla and Takhar [9], Yucel [10], Gorla [11], Khonsari and Brew [12], Khonsari [13], Gorla et al [14], Gorla and Nakayam [15], Char and Chang [16] and Raptis [17]. Rees and Pop [18] studied free convection boundary layer flow of micropolar fluids from a vertical flat plate whereas Desseaux and Kelson [19] studied the same flow bounded by a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Ariman et al (1974) have given an excellent review of micropolar fluids and their applications. Studies of the free, forced, or mixed convection in micropolar fluids past flat, curved, and/or wavy surfaces have been focused on by a number of workers (Ahmadi, 1976;Jena and Mathur, 1981;Gorla et al, 1990;Gorla, 1992;Char and Chang, 1995;Rees and Pop, 1998;Raptis and Takhar, 1999;El-Arabawy, 2003;Hassanien et al, 2004;Ibrahim et al, 2004;Kim, 2004;Sunil et al, 2006;Rahman and Sattar, 2006, 2007;Rahman and Sultana, 2008;Rahman, 2009; Rahman et al, 2009a,b,c) because of the importance of the heat/mass transfer on the flow field of micropolar fluids for determining the quality of the final products.The problem of the stretching sheet has been of great use in engineering studies. Crane (1970) first studied the flow caused by an elastic sheet whose velocity varies linearly with the distance from a fixed point on the sheet.…”
mentioning
confidence: 98%
“…These fluids are used in analyzing exotic lubricants, the flow of colloidal suspensions, paints, liquid crystals, animal blood, fluid flowing in brain, turbulent shear flows, and body fluids both mathematically and industrially. Since the early studies of Eringen [15,16] many researchers have reported results on micropolar fluids (see [17][18][19][20][21][22][23] and the references therein). Hossain and Chaudhury [24] have analyzed mixed convection flow of a micropolar fluid over an isothermal plate with a variable spin gradient viscosity.…”
Section: List Of Symbols Variablesmentioning
confidence: 99%